Involvement of Journalists and Content Creators in Developing Opportunities for Halal Tourism - Setiawan, Erik; Rachmiatie, Atie; Zakiah, Kiki (KnE Social Sciences, 2024)
Based on previous research, halal tourism development in Indonesia has not been optimal and faces various obstacles and constraints both psychological, regulatory, and socio-economical. One of the priority issues in the development of halal tourism is how to change the knowledge, and awareness among journalists and content creators so that the concept of halal tourism can be spread widely in various media. For this reason, this study uses an action research approach with Focus Group Discussion, interviews, and media content analysis, then provides treatment through the dissemination of the concept of halal tourism and fulfillment of halal products in tourist areas. The results showed that there is still an understanding gap about the concept of halal tourism, and a lack of awareness about the importance of developing halal tourism so that stakeholders have limited information about halal tourism produced by journalists and content creators in their respective media. The strategic approach to changing knowledge, awareness, and behavior related to halal tourism is through providing education and information to journalists and content creators, socializing government policies and action plans in an integrated manner, intensifying promotions related to halal tourism, information technology mapping, and community service activities related to halal tourism. Keywords: mindset, journalist and content creators, halal tourism